Analysis of Guard Cell Readouts Using Arabidopsis thaliana Isolated Epidermal Peels - Pantaleno, Rosario (2024)
Stomata are pores surrounded by a pair of specialized cells, called guard cells, that play a central role in plant physiology through the regulation of gas exchange between plants and the environment. Guard cells have features like cell-autonomous responses and easily measurable readouts that have turned them into a model system to study signal transduction mechanisms in plants. Here, we provide a detailed protocol to analyze different physiological responses specifically in guard cells. We describe, in detail, the steps and conditions to isolate epidermal peels with tweezers and to analyze i) stomatal aperture in response to different stimuli, ii) cytosolic parameters such as hydrogen peroxide (H2O2), glutathione redox potential (EGSH), and MgATP-2 in vivo dynamics using fluorescent biosensors, and iii) gene expression in guard cell–enriched samples. The importance of this protocol lies in the fact that most living cells on epidermal peels are guard cells, enabling the preparation of guard cell–enriched samples.